(untitled) (UNWE Yearbook, 2007)
The study aims to identify the connections between the market indices of public limited companies and the development of the capital market under the conditions of a transition to a functioning market economy. The analysis has shown that during the period surveyed - between 2000 and 2005, the indices “net profit” and “net monetary flow” for the public limited companies analyzed were subject to a considerable variation and often took on negative values. This fact indicates a considerable business and financial risk, as well as a virtual absence of profit and net monetary flows management broken down by years.The indices calculated on the basis of net profit and net monetary flows are unsuitable for comparing and assessing the capital market. For this reason the consolidated data reflect the indices “Price/ Receipts per Share”, “Price/ Long-term Assets per Share”, Price/ Assets per Share”; and Price/Equity per share”.In conclusion, it is stated that the results of the policy intended to develop the capital market mark a very favourable trend; however the market incentives should continue under the new conditions after Bulgaria’s accession to the European Union.